BRD4 in physiology and pathology: ''BET'' on its partners. (26th October 2021) - Liang, Yin; Tian, Jieyi; Wu, Tao
Abstract: Bromodomain‐containing 4 (BRD4), a member of Bromo and Extra‐Terminal (BET) family, recognizes acetylated histones and is of importance in transcription, replication, and DNA repair. It also binds non‐histone proteins, DNA and RNA, contributing to development, tissue growth, and various physiological processes. Additionally, BRD4 has been implicated in driving diverse diseases, ranging from cancer, viral infection, inflammation to neurological disorders. Inhibiting its functions with BET inhibitors (BETis) suppresses the progression of several types of cancer, creating an impetus for translating these chemicals to the clinic. The diverse roles of BRD4 are largely dependent on its interaction partners in different contexts. In this review we discuss the molecular mechanisms of BRD4 with its interacting partners in physiology and pathology. Current development of BETis is also summarized. Further understanding the functions of BRD4 and its partners will facilitate resolving the liabilities of present BETis and accelerate their clinical translation. Abstract : BRD4 associates with many proteins, as well as DNA and RNA. These BRD4 complexes transcriptional‐dependently or ‐independently control diverse physiological processes and are related to a variety of pathologies. BRD4 inhibitors may be applied to treat these diseases.